Regenerative effect of platelet-rich fibrin on articular cartilage defects in an experimental rat model - Metineren, Hasan; Dülgeroğlu, Turan Cihan (The European Research Journal, 2019)
Objectives: Different materials are currently being used experimentally to accelerate cartilage healing and to obtain hyaline cartilage. We aimed to investigate the effect of platelet-rich fibrin on joint cartilage healing. Methods: Twenty rats were used in this study. platelet-rich fibrin was obtained from 4 rats, and the remaining 16 rats were randomly divided into two groups (4 and 8 weeks). Both knee joints were prepared, and an osteochondral defect was created at the femoral condyle in all rats. platelet-rich fibrin was placed into the osteochondral defect of the right knee, while the left knee joint was used as a control. Groups were sacrificed after 4 and 8 weeks, respectively. Results: According to the O'Driscoll score, there were no significant differences between the right and left knee scores in group 4 weeks (p = 0.820). However, the right knee scores were significantly different than the left knee scores in group 8 weeks (p < 0.001). Defects were completely filled with cartilage tissue after 8 weeks in the platelet-rich fibrin group. Conclusions: Similar to its role in various tissues, platelet-rich fibrin is an effective biomaterial that enhances the healing of osteochondral defects.